Study of structural complexity of optimal order digital filters for de-noising ECG signal. (2019) - Bhogeshwar, Sande Seema; Soni, M.K.; Bansal, Dipali
Selection and implementation of optimal order digital filter for denoising ECG signal on FPGA, based on Signal to Noise Ratio (SNR), error and accuracy using wavelet toolbox is a tedious task. To overcome this problem, an attempt has been made in MATLAB to obtain a noise-free ECG signal based on SNR and mean square error to select optimal order digital filter. An ECG sample from MIT-BIH arrhythmia database is artificially corrupted by adding noise and is filtered through different low-pass IIR and FIR digital filters. The hardware complexity of optimal order digital filters structure is checked in terms of multipliers, adders and delays in MATLAB and their performance is compared based on the number of basic elements and visual inspections. It is found that the elliptic IIR filter and Kaiser window FIR filter require low-filter order for a given specification and hence, requires less number of basic elements.